Challenges in Integrating International Evidence Relating to Stroke Rehabilitation: Experiences from a Cochrane Systematic Review. Issue 8 (December 2014) - Pollock, Alex; Campbell, Pauline; Baer, Gillian; Choo, Pei Ling; Forster, Anne; Morris, Jacqui; Pomeroy, Valerie M; Langhorne, Peter
There are many randomized controlled trials relating to stroke rehabilitation being carried out in China, which are often published in Chinese-language journals. A recent update to our Cochrane systematic review of physical rehabilitation to improve function and mobility after stroke included 96 trials; over half (51) were conducted in China; 37 of these included studies were published in Chinese. Analyses within this Cochrane review support the conclusion that physical rehabilitation, using a mix of components from different approaches, is effective for the recovery of function and mobility after stroke. The inclusion of the Chinese studies had a substantial impact on the volume of evidence and, consequently, the conclusions. In this paper, we explore whether it is appropriate to draw implications for clinical practice throughout the world from evidence relating to a complex rehabilitation intervention delivered within one particular geographical healthcare setting. We explore the unique challenges associated with incorporating the body of evidence from China, particularly the Chinese-language publications, and identify the ongoing debate about the quality of Chinese research publications. We conclude that the growing body of evidence from China has important implications for future systematic reviews and evidence-based stroke care, but analysis and interpretation raise challenges, and improved reporting is critical.